Insulinoma-Associated Protein 1 (INSM1) as a diagnostic immunohistochemical marker for neuroendocrine differentiation – A tertiary care centre experience - Nair, Gayathri G; Kumar, Aneesha Asok; Nair, Vibha B; Kalakkunath, Sankar; Safar, Sherin (Journal of Pathology of Nepal, 2025)
Background: Neuroendocrine neoplasms represent a heterogeneous group of tumours and require accurate diagnosis and grading for appropriate management. Although conventional synaptophysin and chromogranin-A are the conventional immunohistochemical markers, they have variable sensitivity and specificity. Insulinoma-associated protein 1 has recently emerged as a nuclear marker with promising diagnostic utility. This study aims to compare the sensitivity, and specificity of Insulinoma-associated protein 1 with Synaptophysin and Chromogranin A in neuroendocrine neoplasms of different grades and sites. Materials and Methods: This cross-sectional study included 62 histologically diagnosed cases of neuroendocrine neoplasms and 30 non-neuroendocrine neoplasms retrieved from pathology archives. Expression of Synaptophysin, Chromogranin A, and INSM1 were evaluated using the H-score. Sensitivity, specificity, positive and negative predictive values were calculated and compared. Results: INSM1 showed nuclear positivity in 95.2% of neuroendocrine neoplasms and was negative in all non-neuroendocrine neoplasms. The mean H-score was 232.9± 93.5. INSM1 was highly sensitive (95.1%) and specific (96.7%) compared to synaptophysin but less specific (66%) compared to chromogranin-A. Conclusions: INSM1 was found to be highly sensitive and specific nuclear marker for neuroendocrine differentiation. Its high diagnostic accuracy and characteristic nuclear localization justify its inclusion as a valuable marker in routine immunohistochemical panels.